Endophytic Bacteria From the Roots of the Medicinal Plant Alkanna tinctoria Tausch (Boraginaceae): Exploration of Plant Growth Promoting Properties and Potential Role in the Production of Plant Secondary Metabolites - Rat, Angélique; Naranjo, Henry D.; Krigas, Nikos; Grigoriadou, Katerina; Maloupa, Eleni; Alonso, Alicia Varela; Schneider, Carolin; Papageorgiou, Vassilios P.; Assimopoulou, Andreana N.; Tsafantakis, Nikolaos; Fokialakis, Nikolas; Willems, Anne (Frontiers in Microbiology, 2021)
Alkannin and shikonin (A/S) are enantiomeric naphthoquinones produced in the roots of certain plants from the Boraginaceae family such as Lithospermum spp. and Alkanna spp. They possess antimicrobial, anti-tumoral and wound healing properties. The production of secondary metabolites by Alkanna tinctoria might be influenced by its endomicrobiome. To study the interaction between this medicinal plant and its bacterial endophytes, we isolated bacteria from the roots of wild growing Alkanna tinctoria collected near to Athens and Thessaloniki in Greece. Representative strains selected by MALDI-TOF mass spectrometry were identified by partial 16S rRNA gene sequence analysis. In total, 197 distinct phylotypes of endophytic bacteria were detected. The most abundant genera recovered were Pseudomonas, Xanthomonas, Variovorax, Bacillus, Inquilinus, Pantoea and Stenotrophomonas. Several bacteria were then tested in vitro for their plant growth promoting activity and the production of cell-wall degrading enzymes. Strains of Pseudomonas, Pantoea, Bacillus and Inquilinus showed positive plant growth properties whereas those of Bacteroidetes and Rhizobiaceae showed pectinase and cellulase activity in vitro. In addition, bacterial responses to alkannin and shikonin were investigated through resistance assays. Gram negative bacteria were found to be resistant to the antimicrobial properties of A/S, whereas the Gram positives were sensitive. A selection of bacteria was then tested for the ability to induce A/S production in hairy roots culture of A. tinctoria. Four strains belonging to Chitinophaga sp., Allorhizobium sp., Duganella sp. and Micromonospora sp., resulted in significantly more A/S in the hairy roots than the uninoculated control. As these bacteria can produce cell-wall degrading enzymes, we hypothesize that the A/S induction may be related with the plant-bacteria interaction during colonization.